Assessing The Impact Of Six-Week Training On Countermovement (CMJ) Jump And Depth Jump (DJ) For Enhancing Vertical Jump In Badminton Players - Balo, Abhishek; Prasad, Dr. Sambhu; Sinha, Sandip; Meto, Heta; Ramchiary, Sonam; Mimi, Umesh (Migration Letters, 2022)
This research delves into the nuanced effects of countermovement jump (CMJ) training on the vertical jump ability of 30 male state-level badminton players. Through meticulous allocation, participants were assigned to one of three groups: CMJ, Depth Jump, or Control. Preceded by comprehensive pre-test assessments, a series of targeted interventions ensued, followed by post-test evaluations to gauge the efficacy of CMJ training. Employing rigorous statistical methodologies, including ANCOVA and pairwise comparisons, the study unveils compelling insights. Results underscore a remarkable enhancement in vertical jump proficiency among CMJ participants relative to their Depth Jump and Control counterparts, with statistically significant mean differences of 3.120 (p = .024) and 3.300 (p =.018), respectively. These findings not only highlight the pronounced efficacy of CMJ training but also underscore its potential as a cornerstone in the optimization of athletic performance within the realm of badminton. Such empirical evidence provides invaluable insights for coaches, athletes, and sports scientists, informing evidence-based strategies aimed at maximizing athletic potential and fostering competitive excellence.